The study of influence factors in x-ray computed tomography using simulation approach. - Yang, Xiuyuan (Cranfield University, 2018)
XCT simulation scanning was used throughout the study because simulation scanning has the flexibility in changing scanning parameters as well as improving the efficiency. The research investigated the effect of voltage, scattering-contamination and multi-sampling on the quality of 2D image projection. For The study tested factors of scattering-contamination, multi-sampling and cone-beam angle on dimensional measurement error with the numerical geometry samples including spheres, cubes, cylinders and tubes. For cylinders and tubes, the measurement of outer diameter leaded more deviation than inner diameter. Scattering contamination had limited influencing (up to 1/35 of the voxel size) to the measurement result but scattering contamination can amplify the operator factor in the geometry determination step. 3X3 multi-sampling detector could optimise the measurement result when measuring the diameter of the cylinder. On the other hand, the effectiveness of the application of multi-sampling is related to the geometry features for measure, and the effect is independent to the scattering-contamination. When measuring circles on the tube, the cone-beam angle had only slight influence (up to 1/131 of voxel size) on the measurement error.
Keywords: Cone beam angle; multi-sampling; scattering; sphere; additive manufacturing; voltage; current